The effect of fluoridated etching on the shear bond strength of orthodontic brackets an in vitro study - Isagon, Francina I.
Enamel demineralization that occurs adjacent to directly bonded orthodontic brackets is of great concern to orthodontists. Among the many procedures suggested to overcome this problem is the addition of fluoride to phosphoric acid etching solution. The purpose of this study was to evaluate the bond strength and debonding interface distribution of adhesive, with and without the use of fluoridated etchant on the enamel, before bonding. Experimental group of forty-six bovine incisors were etched with 37% H3PO4 solution incorporated with 1.23% sodium fluoride (NaF) for 15 seconds. The control group of 46 teeth was etched with 37% H3P04 without fluoride for 15 seconds. Brackets were bonded to the labial surfaces of the crowns of both groups of teeth. Bracketed teeth were tested with an Instron machine, to determine the shear bond strength. After debonding, the surfaces of the teeth were examined to determine the adhesive remaining and distributive percentages of debonding interfaces. The results showed that there isno significant difference in the mean shear bond strength value of the two groups tested. The debonding interface distribution was statistically significantly different (p<.001). The results suggest that there is an association between the type of group and the ARI score. Hence, the fluoridated etching with 1.23% NaF may have a clinical application in the prevention of demineralization surrounding orthodontic brackets.
Vita.
Thesis (Master of Science in Dentistry) -- University of the Philipines, Manila
Keywords: Fluoridation; Orthodontics